Semantic models of phraseological units denoting adverse emotions and feelings - Liliya Vyazirovna Bazarova, Emma Nikolaevna Gilyazeva,; Bulanova, Leisan Nailevna (Opción, 2019)
The present paper investigates into the semantic features, internal form and meaning of phraseological units (PU) expressing adverse emotions and feelings of a person in the English (EL) and German (GL) languages via a detailed comparative analysis of the semantic models of phraseological units. As a result, most of the PU denoting adverse emotions and feelings of a person are metaphorical and figurative. In conclusion, national-cultural characteristics have a direct explanation of the differences even in closely related languages.